2020
DOI: 10.3897/nl.43.38686
|View full text |Cite
|
Sign up to set email alerts
|

Nearctic walnut leafminers invade Europe: first Coptodisca lucifluella (Clemens, 1860) and now Coptodisca juglandiella (Chambers, 1874) (Lepidoptera, Heliozelidae)

Abstract: The Nearctic leafminer of black walnut Coptodisca juglandiella (Chambers, 1874) was found in Hungary and reported as new for Europe. Larvae were found in leafmines on black walnut (Juglans nigra (L.)), white walnut (J. cinerea (L.)) and Arizona walnut (J. major (Torr.)); the latter two Juglans species are new host plant records for C. juglandiella. Mines of Coptodisca lucifluella (Clemens, 1860), another Nearctic invader, were found on leaves of bitternut hickory (Carya cordiformis (Wangenh.) K.Koch) and Cauca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 11 publications
0
25
0
3
Order By: Relevance
“…Процес проникнення нових адвентивних комахфілофагів на територію України продовжуватиметься й надалі. Зокрема в Угорщині виявлено нові для Європи види північноамериканських мінуючих молей Coptodisca lucifl uella (Clemens, 1860) та C. juglandiella (Chambers, 1874), личинки яких живляться на листках дерев з родів Juglans, Carya та Pterocarya (Takács et al, 2020). Поява цих видів на території Закарпаття -справа короткого часу.…”
Section: рис 7 хлороз листків платана після пошкодженняunclassified
“…Процес проникнення нових адвентивних комахфілофагів на територію України продовжуватиметься й надалі. Зокрема в Угорщині виявлено нові для Європи види північноамериканських мінуючих молей Coptodisca lucifl uella (Clemens, 1860) та C. juglandiella (Chambers, 1874), личинки яких живляться на листках дерев з родів Juglans, Carya та Pterocarya (Takács et al, 2020). Поява цих видів на території Закарпаття -справа короткого часу.…”
Section: рис 7 хлороз листків платана після пошкодженняunclassified
“…The walnut shield bearer C. lucifluella is a micro leaf miner moth in the family Heliozelidae. A number of eight indigenous species and four invasive species belonging to this family are reported to be present in the European territory until now (Van Nieukerken et al, 2018, Takács et al, 2020. C. lucifluella is one of the four invasive species, native to North America, together with Antispila oinophylla (Van Nieukerken & Wagner, 2012), C. splendoriferella (Clemens, 1860) and C. juglandiella (Chambers, 1874) (Takács et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, the species was signalled for the first time in Mexico in various pecan nut orchards (Ávila-Rodríguez et al, 2015) and in 2017, this is reported in Hungary (Takács et al, 2017). A more extensive survey in 263 localities dispersed throughout Hungary proves the vast spread of the species (Takács, et al, 2020). In 2019, C. lucifluella was identified in Ukraine in the proximity of the Hungarian border (Pályi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The small leafmining family Heliozelidae has recently been the subject of several papers, including papers on phylogeny and classification (van Nieukerken and Geertsema 2015;Milla et al 2017Milla et al , 2019 van Nieukerken and Eiseman 2020), records of three new invasive species in Europe (Bernardo et al 2011(Bernardo et al , 2015van Nieukerken et al 2012;Takács et al 2020) and treatments of difficult species pairs that were previously considered single species (Mutanen et al 2007;van Nieukerken et al 2018). Of the thirteen known European species, nine of which are native (van Nieukerken et al 2018;Takács et al 2020), the small Antispilina ludwigi Hering, 1941, the only one feeding on a herbaceous plant, remains relatively poorly known. Hering (1941) described the species and genus on the basis of moths reared from leafmines on Snake-root (or Common Bistort), Bistorta officinalis Delarbre (also known as Polygonum bistorta L. or Persicaria bistorta (L.) Samp.…”
Section: Introductionmentioning
confidence: 99%